Anti-Severe Acute Respiratory Syndrome Coronavirus 2 Immunoglobulin G Antibody Seroprevalence Among Truck Drivers and Assistants in Kenya. (12th June 2021) - Kagucia, E Wangeci; Gitonga, John N; Kalu, Catherine; Ochomo, Eric; Ochieng, Benard; Kuya, Nickline; Karani, Angela; Nyagwange, James; Karia, Boniface; Mugo, Daisy; Karanja, Henry K; Tuju, James; et al.
Abstract: In October 2020, anti-severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) immunoglobulin G seroprevalence among truck drivers and their assistants (TDA) in Kenya was 42.3%, higher than among healthcare workers and blood donors. Truck drivers and their assistants transport essential supplies during the coronavirus disease 2019 pandemic, placing them at increased risk of being infected and of transmitting SARS-CoV-2 over a wide geographical area.